Le pouvoir de l’amour - EMMA (Emma, 2020)
Salut à toutes et tous, en ces temps confinés j’ai pensé vous mettre à disposition cette histoire inédite de mon tome 3 « La charge émotionnelle ». Je souhaite plein de …
Keywords: approches et analyses; bande-dessinée; care; charge mentale; discipline; discours dominant; femmes*; hétérosexisme; identités LGBTQIA2+; pédagogie; ressource en ligne; santé; sciences humaines; sexualité; sociologie; systèmes d'oppressions; thématiques; travail; travail domestique

Sex & gender: An introduction - Lips, Hilary M. (Waveland Press, Inc., 2020)
Are sex and gender really two different things? How malleable is gender identity? Do both gender and sex have to be conceptualized as binaries—as having two distinct but complementary categories? Should we emphasize gender differences, or is that the wrong question? When should we call a gender difference “small”? Are women really “nonaggressive” or does that label stem from stereotyping? How does subtle or “modern” sexism work on its targets? Scholarship on these and other gender-related questions has exploded in recent years. Hilary Lips synthesizes that research for students in an accessible and readable way. Concepts on sex and gender are presented with the social context in which they were developed. As in previous editions, Lips takes a multicultural approach, discussing the gender experiences of people from a wide range of races, cultures, socioeconomic statuses, and gender and sexual identities. She emphasizes empirical research but takes a critical approach to that research.
Keywords: analyse différenciée selon les sexes -ADS+; approches et analyses; biologie; construction du savoir; corps; cours; discipline; discours dominant; essentialisation; hétérosexisme; identité; identité sexuelle; inégalités; premier cycle; psy4910; psychologie; santé; sciences humaines; sexe/genre; sexisme; sexualité; stéréotypes de genre; systèmes d'oppressions; thématiques; trs3550; études de genres

Comment la crise fait-elle ressortir les inégalités de genre ? - Plumauzille, Clyde (2020)
Aides-soignantes, caissières, aides à domicile… ce sont majoritairement des femmes qui se retrouvent en première ligne contre le virus. Comme le rappelle l’historienne Clyde Plumauzille dans ce podcast, ces inégalités ne sont pas nouvelles, la prise en charge d’autrui au sein du foyer ou dans la société étant historiquement dévolue aux femmes.
Performers: _:n2788
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; care; charge mentale; confinement; covid-19; histoire et politique; hétérosexisme; inégalités; projet charge mentale; périodes historiques; rapports sociaux de sexe; ressource en ligne; santé; sexisme; systèmes d'oppressions; thématiques; travail; travail domestique; violences; violences conjugales